Pregnancy with Idiopathic Thrombocytopenic Purpura - A Case Report - Akther, R; Hossain, T; Khan, MA; Rashid, Maliha (Journal of Bangladesh College of Physicians and Surgeons, 2010)
Thrombocytopenia in pregnancy has many common causes, including gestational thrombocytopenia, viral and bacterial infections, and preeclampsia complicated by hemolysis, elevated liver enzymes, and low platelet (HELLP) syndrome. The great concern for ITP during pregnancy is the risk of thrombocytopenia in the newborn infant. A 30yrs old 3rd gravid women was admitted in maternity unit 3, Dhaka Medical College Hospital with the complaints of 36weeks pregnancy, lower abdominal pain and less fetal movement. She had been suffering from severe thrombocytopenia for the last 8 months. She treated with Prednisolone during pregnancy period, platelet transfusion before and after delivery and Danazol in puerperium. Her baby was delivered by caesarean section .Her intra-operative and post operative period was uneventful. She delivered a healthy male baby weighted 2.5 kg and breast feeding established successfully. She was discharged on seventh post operative day. The aim of this case report to reveal pregnancy with ITP and its clinical presentation, investigation and management with review of relevant literatures. DOI: 10.3329/jbcps.v28i3.6516 J Bangladesh Coll Phys Surg 2010; 28: 196-198